Implementasi Metode Peer Feedback dalam Meningkatkan Hasil Belajar Siswa Kelas 8 pada Mata Pelajaran PAI di SMP Negeri 7 Kota Bangun Seberang - Eka Sri Rahmawati; Laili Azqia; Yuliyani Lestari; Akhmad Riadi (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2024)
This study explores the implementation of the peer feedback method in improving the learning outcomes of grade VIII students in Islamic Religious Education (PAI) subjects at SMP Negeri 7 Kota Bangun Seberang. Using the Classroom Action Research (CAR) approach, this study aims to improve student engagement and learning outcomes through active participation in providing feedback to others. This method was chosen to overcome student boredom with conventional learning methods such as lectures. The results of the study indicate that the application of peer feedback can improve students' understanding and motivation to learn. The research process involved two cycles of action including planning, implementation, observation, and reflection. Data collected through observation and testing were analyzed descriptively qualitatively and quantitatively. The findings showed a significant increase in student learning activities and learning outcomes, indicating that the peer feedback method is effective in facilitating collaborative and supportive learning. This study concludes that peer feedback not only functions as an assessment tool, but also as a means of developing students' character and communication skills.